2015
DOI: 10.1177/0004867415569797
|View full text |Cite
|
Sign up to set email alerts
|

Suicide-related Internet use: A review

Abstract: Research has shown that individuals use the Internet to search for suicide-related information and to discuss suicide-related problems with one another. However, the causal link between suicide-related Internet use and suicidal thoughts and behaviours is still unclear. More research is needed, particularly involving direct contact with Internet users, in order to understand the impact of both informal and professionally moderated suicide-related Internet use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
1
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 55 publications
1
51
1
9
Order By: Relevance
“…Previous research has found that, indeed, online suiciderelated activity may be associated with later suicidal behavior. [25][26][27] For example, Fink et al 28 examined whether suicide deaths in the United States increased in the 4 months after Robin Williams' death while controlling for typical seasonal patterns of suicides. They found that suicide deaths were nearly 10% greater than expected-meaning that in addition to the thousands of people in the United States who die by suicide every month, more than 2,000 additional suicide deaths were observed after Robin Williams' death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has found that, indeed, online suiciderelated activity may be associated with later suicidal behavior. [25][26][27] For example, Fink et al 28 examined whether suicide deaths in the United States increased in the 4 months after Robin Williams' death while controlling for typical seasonal patterns of suicides. They found that suicide deaths were nearly 10% greater than expected-meaning that in addition to the thousands of people in the United States who die by suicide every month, more than 2,000 additional suicide deaths were observed after Robin Williams' death.…”
Section: Discussionmentioning
confidence: 99%
“…Coupling Fink et al results with the current findings, it is possible that Internet searches for suicide-related terms are related to increases in suicidal behavior. [25][26][27][28] Indeed, search volumes for suicide and depression are not only associated with the incidence of suicidal behavior in England, they also significantly improve the ability to predict the rate of suicide. 16…”
Section: Discussionmentioning
confidence: 99%
“…Cases of social media being used by individuals to express suicidal thoughts, look for suicide methods, or even live broadcast suicidal behaviors have been reported and studied in different countries [15-17] including China [18,19]. With Twitter and Facebook blocked in China, Sina Weibo (referred to as Weibo hereafter; Sina is a company name and Weibo literally means Microblog) is one of the most popular social media platforms among the Chinese population.…”
Section: Introductionmentioning
confidence: 99%
“…3 Data generated by users' web search query behavior in Internet search engines have been used to address a large number of medical problems, ranging from epidemiological aspects of various diseases 4,29 to monitoring suicide risk 30,31 or nonsuicidal self-injury 32 in a defined population. Accordingly, data related to web search query behavior has been also harnessed in pharmacovigilance for, for example, drug safety issues.…”
Section: Discussionmentioning
confidence: 99%